1992
DOI: 10.1159/000154061
|View full text |Cite
|
Sign up to set email alerts
|

Serum Protein Groups (Hp, GC, C3) in Patients with Gastric Carcinoma

Abstract: The phenotypes and gene frequencies of 3 serum protein systems (Hp, GC and C3) were studied in 114 consecutive patients from all over Greece with gastric carcinoma. Healthy Greeks studied previously in our Department served as controls. No significant differences were found between patients and controls concerning Hp. Significant differences were found in the GC and C3 systems; GC 2-1 and C3F phenotype as well as C3*F gene frequencies were significantly higher in patients than in controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Electrophoret ic immunofixation on cellulose acetate strips, accord ing to Grumbaum and Zajak [10] It is interesting that similar results for Crohn's disease but not for ulcerative colitis were obtained by others [7] in a sample of 125 patients (72 with ulcerative colitis, 53 with Crohn's disease) examined. Positive associa tions of C3*F have also been found for other chronic inflammatory conditions such as rheumatoid arthritis and multiple sclerosis by others [12][13][14], and for peptic ulcer [2] and gastric cancer [3], but not for colon cancer [4] by our group. It has been reported [15] that C3F and C3S differed in their capacity to bind to mononuclear cells in vitro: C3F had an enhanced capacity to bind with the respec tive receptor on mononuclear cells.…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…Electrophoret ic immunofixation on cellulose acetate strips, accord ing to Grumbaum and Zajak [10] It is interesting that similar results for Crohn's disease but not for ulcerative colitis were obtained by others [7] in a sample of 125 patients (72 with ulcerative colitis, 53 with Crohn's disease) examined. Positive associa tions of C3*F have also been found for other chronic inflammatory conditions such as rheumatoid arthritis and multiple sclerosis by others [12][13][14], and for peptic ulcer [2] and gastric cancer [3], but not for colon cancer [4] by our group. It has been reported [15] that C3F and C3S differed in their capacity to bind to mononuclear cells in vitro: C3F had an enhanced capacity to bind with the respec tive receptor on mononuclear cells.…”
Section: Methodssupporting
confidence: 77%
“…Among other factors, infection, allergy to dietary components and immune responses to bacterial or self-antigens have been implicated. Some serum protein groups (Hp, GC, C3, Gm, Inv) have been already studied in our department and some interest ing associations with peptic ulcer, gastric can cer, colon cancer and liver diseases have been found [2][3][4][5][6].…”
mentioning
confidence: 99%
“…In a previous study of patients with gastric carci noma we found that the GC 2-1 and C3F phe notypes as well as C3*F gene frequency were significantly higher in patients than in con trols [3].…”
Section: Introductionmentioning
confidence: 70%
“…Although C3 is primarily synthesized by hepatocytes 4 , other tissues and cells also have the capability to synthesize C3 such as macrophages 7 , dendritic cells 8 , polymorphonuclear leukocytes 9 , proximal tubular epithelial cells 1012 , fibroblasts 13 , uterine epithelia 14 , pneumonocytes 15 , and activated T cells 16 , indicating that it may possess pleiotropic physiological function. Besides its implications in various congenital and acquired complement deficiencies, C3 is involved in glomerular disease 17 , hemolytic uremic syndrome 18 , and gastric carcinoma 19 . Based on its pivotal roles in complement activation and multiple biological functions, researchers have been prompted to address both pathological and physiological activities of C3 using C3-deficient animal models.…”
Section: Introductionmentioning
confidence: 99%